Integrating Specialty Coffee into Pilgrimage Tourism: Cultural and Economic Opportunities in Makkah and Madinah - Maspul, Kurniawan Arif (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2025)
The integration of specialty coffee in the holy cities of Makkah and Madinah offers a unique opportunity to enhance the visitor experience, drive economic growth, foster cross-cultural exchange, and promote sustainability. This qualitative study, based on interviews, site visits, and thematic analysis, explores how specialty coffee contributes to visitor satisfaction, local entrepreneurship, and cultural preservation. The findings indicate that the specialty coffee sector can promote economic diversification, generate employment, and foster business opportunities. By highlighting indigenous coffee varieties and preserving traditional practices, both cities have the potential to become recognized cultural destinations. Moreover, understanding consumer preferences can inform effective marketing strategies, helping to position Saudi specialty coffee in the global market and attract international coffee enthusiasts. The sector also supports sustainability through fair trade and environmentally responsible practices, benefiting local growers and advancing ethical standards. We conclude with recommendations for policy and business strategies that align with both local values and global tourism trends.